Development of HPLC Protocol and Simultaneous Quantification of Four Free Flavonoids from Dracocephalum heterophyllum Benth. - Sodik Rakhmonovich Numonov; Muhammad Nasimullah Qureshi; Haji Akber Aisa (International Journal of Analytical Chemistry)
Quantification of the four flavonoids, namely, luteolin, kaempferol, diosmetin, and chrysosplenetin, has been performed for the first time in 80% ethanolic extract of Dracocephalum heterophyllum B. through HPLC coupled to UV detector after optimization of extracting solvent and chromatographic conditions. Total flavonoids quantified were 0.324 mg/mL of the extract. HPLC analysis delivered contents of the luteolin, kaempferol, diosmetin, and chrysosplenetin as 0.08%, 0.14%, 0.28%, and 0.79% of the dried extract, respectively. LOD (%) values calculated were 0.04, 0.03, 0.03, and 0.08 and LOQ (%) values were 0.08, 0.12, 0.11, and 0.28 for luteolin, kaempferol, diosmetin, and chrysosplenetin, respectively. The recovery percentages for these flavonoids were within the acceptable range of 95% to 105%. Standard deviation and %RSD were calculated for each target analytes individually in extract for determining the reproducibility and accuracy of the method. In no case the %RSD was higher than 1 taking retention time as a factor while in the case of area under the curve maximum %RSD was noted in the case of diosmetin as 2.85. From our literature review regarding the plant species under study, it appears that these flavonoids have not been quantified before and are reported for the first time in this paper.